Synthesize and Characterization of Aluminum Oxide (Al2O3) Nanoparticle from Aluminum Waste for Nano fluid Application - Darmawan, Darmawan; Syarif, Dani Gustaman; Rudyardjo, Djony Izak (Universitas Airlangga, 2020)
The research of Synthesis and Characterization of Aluminum Oxide (Al2O3) Nanoparticle from Aluminum Waste for Nanofluids has been done. The purpose from this research are knowing the influence of heating temperature tonanoparticle Al2O3 forming and the influence of composition to physico-chemical characteristic of nanofluids Al2O3.The heating temperature variation that that use of 6000C, 7000C, and 8000C. While the composition variation that use of 0.1 gram, 0.2 gram, 0.3 gram, and 0.5 gram. Aluminium Oxide nanoparticle were synthesized by heating Al(OH)3 as precursor derived from aluminum waste precipitation. Aluminum Oxide nanoparticle were suspended with 100 ml of Aquades and dispersed with ultra sonicated to produce Al2O3 nanofluids. Al2O3 nanoparticle has been obtained doing the characterization are the test of XRD (X-Ray Diffraction), SAA (Surface Area Analyzer), Density, Viscosity, CHF (Critical Heat Flux) and Zeta Potential. XRD data showed that the crystallized peak from Al2O3 nanoparticle are gamma alumina with the crystallite size of 6,5 nm (Debye-Scherrer Method). The Surface Area test result from Al2O3 nanoparticle is 149,98 m2/gram and obtained shape of11 nm. According zeta potential data, Nano fluids were stable at pH of 6,3 with zeta potential of 36,70 - 43,53 mV. The density test result obtained with the highest value about 1,503 g/cm3, The viscosity test of 0.92 mPa.s at the composition variation of 0.5 gram. The Nano fluids of the surface decreased 40% after 7 days. CHF test result of Al2O3 nanofluids obtained enhancement about 53,21% at the composition variation of 0.5 gram compared to that of Aquades.